Health-related quality of life after TBI: a systematic review of study design, instruments, measurement properties, and outcome - Polinder, Suzanne; Haagsma, Juanita A; van Klaveren, David; Steyerberg, Ewout W; van Beeck, Ed F (Population health metrics, 2015)
Measurement of health-related quality of life (HRQL) is essential to quantify the subjective burden of traumatic brain injury (TBI) in survivors. We performed a systematic review of HRQL studies in TBI to evaluate study design, instruments used, methodological quality, and outcome. Fifty-eight studies were included, showing large variation in HRQL instruments and assessment time points used. The Short Form-36 (SF-36) was most frequently used. A high prevalence of health problems during and after the first year of TBI was a common finding of the studies included. In the long term, patients with a TBI still showed large deficits from full recovery compared to population norms. Positive results for internal consistency and interpretability of the SF-36 were reported in validity studies. The Quality of Life after Brain Injury instrument (QOLIBRI), European Brain Injury Questionnaire (EBIQ), Child Health Questionnaire (CHQ), and the World Health Organization Quality of Life short version (WHOQOL-BREF) showed positive results, but evidence was limited. Meta-analysis of SF-36 showed that TBI outcome is heterogeneous, encompassing a broad spectrum of HRQL, with most problems reported in the physical, emotional, and social functioning domain. The use of SF-36 in combination with a TBI-specific instrument, i.e., QOLIBRI, seems promising. Consensus on preferred methodologies of HRQL measurement in TBI would facilitate comparability across studies, resulting in improved insights in recovery patterns and better estimates of the burden of TBI.